2022
DOI: 10.1038/s41598-022-15491-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated image curation in diabetic retinopathy screening using deep learning

Abstract: Diabetic retinopathy (DR) screening images are heterogeneous and contain undesirable non-retinal, incorrect field and ungradable samples which require curation, a laborious task to perform manually. We developed and validated single and multi-output laterality, retinal presence, retinal field and gradability classification deep learning (DL) models for automated curation. The internal dataset comprised of 7743 images from DR screening (UK) with 1479 external test images (Portugal and Paraguay). Internal vs ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that DL can predict progression of 2 or more ETDRS grades from fundus images [19], however the cohort size was small and images were from 7-field photography in clinical trial participants with macula oedema and hence are not representative of a screening programme population. Other studies have considered prediction of progression of DR using DL but did not quantify the improvement above current grading [20,21]. With respect to screening policy, a number of approaches have been proposed to improve screening programmes.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…It has been demonstrated that DL can predict progression of 2 or more ETDRS grades from fundus images [19], however the cohort size was small and images were from 7-field photography in clinical trial participants with macula oedema and hence are not representative of a screening programme population. Other studies have considered prediction of progression of DR using DL but did not quantify the improvement above current grading [20,21]. With respect to screening policy, a number of approaches have been proposed to improve screening programmes.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The deep-learning AutoMorph is a publicly available pipeline that uses retinal vasculature morphology on fundus photographs through image preprocessing, quality grading, anatomical segmentation, and morphological feature measurement 56 . The opensource Nderitu et al algorithm detects laterality, retinal field, retinal presence, and gradability 57 .…”
Section: Automatic Quality Assessmentmentioning
confidence: 99%